Drinking Water Emergency Planning and Response in New Hampshire. Issue 1 (23rd January 2023) - Cramton, Megan; Berg, Sara; Bixler, Taler S.; Huang, Jingyan; Mo, Weiwei
Key Takeaways: Eight drinking water industry professionals in New Hampshire were interviewed about their roles and attitudes regarding decision‐making in emergency planning and response. Among the participants, concerns and priorities differed about frequent, well‐understood emergencies and less likely emergencies that had not been previously experienced. There was consensus in terms of the importance of networking and knowing other stakeholders' capabilities as well as the overall benefits of emergency planning and asset management.